Analisis Komprehensif Permasalahan Keimigrasian pada Pos Lintas Batas Negara (PLBN) di Kalimantan Barat dalam Rangka Optimalisasi Pengawasan, Pelayanan, dan Penegakan Hukum Keimigrasian di Wilayah Perbatasan - Aziz Dharmawan Nur Syahputra; Bagas; Delon Agustinus Saragih (Bhirawa Law Journal, 2026)
Border Crossing Posts (PLBN) have a strategic role in maintaining national sovereignty, particularly in immigration aspects. West Kalimantan, as a region directly bordering Malaysia, has several PLBNs that serve as the main gateways for the movement of people and goods between countries. In practice, there are still various problems affecting the effectiveness of immigration functions, including limited human resources, weak supervision of unofficial routes, and uneven infrastructure across PLBN locations. In addition, potential immigration violations such as the use of invalid documents, overstaying, and illegal cross-border activities remain significant challenges that must be addressed. This study aims to analyze immigration issues at PLBNs in West Kalimantan and examine the efforts made to improve supervision, services, and law enforcement. The research method used is a qualitative approach with a literature study based on scientific journals, books, and official reports. The results indicate that it is necessary to enhance inter-agency coordination, strengthen the capacity of officers, and implement digital-based technology to improve the effectiveness of immigration supervision in border areas in a sustainable and integrated manner.